Wild Pitcher Plant (Nepenthes: Nepenthaceae) in Lowland of Tanjung Selor: A Notes of Diversity, Conservation and Threats - Sarah Agustiorini; Sakina Rizqiani; Surianto Effendi (Jurnal Biologi Tropis, 2022)
Borneo is the second-highest diversity island for Nepenthes, with approximately comprising 23 species that were spread on this island. Species found on lowland to highland with variety habitat and ecological types. Tanjung Selor is the capital city of Bulungan Regency, North Kalimantan. Nepenthes distribution in these areas has never been reported, particularly in the heath forest. The study was conducted to report the floristic of Nepenthes in Tanjung Selor. We used a desktop study and field exploration on heath forest of Tanjung Selor in 2019 with rapid biodiversity assessment method. The preliminary report of Nepenthes in Bulungan are presented with species description, ecology, threats, illustration, and a brief disscusion regarding the species. We reported six wild species and one natural hybrid of Nepenthes based on exploration. Nepenthe’s habitat is in an open area, roadside, and heath forest vegetation. The threats are higher from habitat degradation and land conversion to agricultural land or non-agricultural uses.  In this paper, we mentioned Nepenthes fusca growth in lowland habitat, commonly found in highland.